Evaluation of Internet News through a Strategic Communication Document for Combating Addiction - Balica, Kemal; Kirlioğlu, Mehmet (Addicta: The Turkish Journal on Addictions, 2025)
This study investigates the influence of addiction-related language in digital news on societal perceptions and stigma. It highlights the crucial role of journalists in Türkiye in reporting addiction with increased accuracy and sensitivity. Using the Strategic Communication Document for Combating Addiction by the Turkish Ministry of Health as a framework, 181 news articles from five leading Turkish news websites— Hürriyet, Milliyet, Habertürk, Sabah, and Sözcü—were analyzed. The results show that 55.8% of the articles used inappropriate language, whereas only 1.1% adhered to the recommended guidelines. This indicates a considerable gap in the effective application of these guidelines. The findings indicate that the media’s portrayal of addiction may deter individuals from seeking treatment and that the Strategic Communication Document for Combating Addiction’s recommendations have not been effectively incorporated into digital news coverage. Common issues include negative stereotypes about people with addiction, sensationalizing drug-related news, and stressing the economic value of illegal substances. Greater adherence to ethical standards in addiction coverage and comprehensive journalist training programs are essential for promoting ethical and responsible reporting on addiction, reducing stigma, and fighting misinformation. The results reveal a substantial gap between recommended practices and actual reporting, highlighting the need for improved media literacy.